Effects of gamma-irradiation on caprolactam level from multilayer PA-6 films for food packaging: Development and validation of a gas chromatographic method - Araujo, Henrique Peres [UNESP]; Felix, Juliana Silva [UNESP]; Manzoli, Jose Eduardo; Padula, Marisa; Monteiro, Magali [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
A gas chromatographic method to determine caprolactam in multilayer PA-6 films used for meat foodstuffs and cheese was developed and validated. A wide linear range (0.8-400 mu g/ml), RSD <= 4.1% and recovery higher than 90.0% were obtained for the chromatographic system, while precision and accuracy of the method showed RSD <= 3.8%, recovery from 95.5-100.0% and LOQ of 32 mu g/g. Irradiated (3, 7 and 12 kGy) and non-irradiated commercial films were analyzed. Most of them increased caprolactam levels with the increase of irradiation doses. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: gamma-irradiation; caprolactam; food-packaging multilayer films; polyamide 6; GC; validation